PENGARUH VARIASI UKURAN SPROCKET GEAR PADA SEPEDA MOTOR YAMAHA BYSON TERHADAP DAYA DAN TORSI - Farid Afrian, Muhammad; Budiyono, Budiyono; Prasetyo, Imam (Surya Teknika : Jurnal Ilmiah Teknik Mesin, 2021)
Motorcycles must be equipped with a system that is able to bridge the engine output (engine power and torque) with the demands of road conditions, the sprocket is the last part of the power transfer system, because the sprocket is the part that transmits the engine power to the rear wheels through the chain. In previous studies, the average sprocket size variation with teeth larger or smaller is 2 to 4 teeth from the standard sprocket, while the research that will be carried out is using variations in the number of teeth based on the assumptions of friends who use Yamaha motorcycles. Byson 150 cc, because it is based on the assumptions of different users. The purpose of this final project is to determine the effect of sprocket size variations of 14-40 T, 14-44 T and 15-44 T on power and torque on a 150 cc Yamaha Byson motorcycle. This final project was carried out using the data collection method from the dynotest test, using a dynometer. The test results with variations of sprocket gear sizes 14-40 T, 14-44 T and 15-44 T, produce the most optimal power and torque on sprocket gear sizes 15-44 T with a maximum power of 12.8 HP at 7000 RPM and a torque of 14.81 Nm at 4750 RPM this power achievement is due to the difference in ratios that can make the motorcycle accelerate faster, but produce a slightly slower top speed than the standard.Keywords: Sprocket, Power and Torqu